Superfluid Black Holes - Hennigar, Robie A. (2017)
We present what we believe is the first example of a “λ-line” phase transition in black hole hermodynamics. This is a line of (continuous) second order phase transitions which in the case of liquid 4He marks the onset of superfluidity. The phase transition occurs for a class of asymptotically anti–de Sitter hairy black holes in Lovelock gravity where a real scalar field is conformally coupled to gravity. We discuss the origin of this phase transition and outline the circumstances under which it (or generalizations of it) could occur.